The algebraic analysis of strongly connected graphs networks - Волков, А. А. (Problems of Informatization and Control, 2004)
The strongly coherent columns of a network it is represented as finite-dimensional of the vector space caused by his parts with bases, determined on him, mutually orthogonal subspace of independent generalized units and independent cycles. The device of linear algebra for a substantiation of methods of reception of the matrix operators of linear transformations of the independent generalized units both independent cycles and definition of their interdependence is used